Cointegration Analysis: An International Enterprise. - Hendry, D (University of Copenhagen, 1997)
Cointegration analysis is truly an international enterprise, with researchers from most continents and major countries participating. You will, of course, recognize that the very word is Danish, in the same sense as menu is English. The history of the concept and related notions, as this is central to understanding its present position in the econometrician’s toolkit is recalled. Then the idea is illustrated with an example of how we conceive of cointegration in the context of an issue such as inflation, which has been the centre of much economic policy and even more theoretical and empirical analysis.